2015
DOI: 10.3390/microorganisms3040746
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Starvation Induces Cross-Resistance to Thermal, Acid, and Oxidative Stress in Serratia marcescens

Abstract: The broad host-range pathogen Serratia marcescens survives in diverse host and non-host environments, often enduring conditions in which the concentration of essential nutrients is growth-limiting. In such environments, carbon and energy source starvation (carbon-starvation) is one of the most common forms of stress encountered by S. marcescens. Related members of the family Enterobacteriaceae are known to undergo substantial changes in gene expression and physiology in response to the specific stress of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Significant treatment effects on growth parameters of the ancestor indicate that the conditions were suitable for the culture of Serratia, and that the chemical manipulations of the culture medium were physiologically relevant for Serratia. Consistent with prior observations on several taxa, including Serratia [4952], the greatest impact on yield was due to lower energy (glucose) supply, followed by lower supplies of bulk elements (N, P), while impacts of lower trace metal supplies were relatively muted (figure 1). As discussed in Warsi et al .…”
Section: Discussionsupporting
confidence: 88%
“…Significant treatment effects on growth parameters of the ancestor indicate that the conditions were suitable for the culture of Serratia, and that the chemical manipulations of the culture medium were physiologically relevant for Serratia. Consistent with prior observations on several taxa, including Serratia [4952], the greatest impact on yield was due to lower energy (glucose) supply, followed by lower supplies of bulk elements (N, P), while impacts of lower trace metal supplies were relatively muted (figure 1). As discussed in Warsi et al .…”
Section: Discussionsupporting
confidence: 88%
“…Another significant factor to consider with environmental induction of pathogen virulence is cross-protection, that is, resistance to multiple environmental stressors derived from bacterial exposure to a specific environmental stressor ( Capozzi et al, 2009 ; Alvarez-Ordóñez et al, 2015 , 2017 ). For example, several studies have shown that starvation stress induces heat tolerance and resistance to oxidative stress in pathogenic E. coli and Serratia marcescens ( Jenkins et al, 1988 ; Leenanon and Drake, 2001 ; Pittman et al, 2015 ).…”
Section: Repair Adaptation Subsequent Cross-protection Against Strementioning
confidence: 99%
“…Recently, Wu et al reported the reduction of ATP levels in starved cells of mycobacteria [ 17 ]. Other studies reported that bacteria under starved conditions had increased tolerance against environmental stresses, e.g., salt, hyperosmotic pressure, desiccation, heat, and ultraviolet (UV) radiation [ 3 , 16 , 18 ]. Transcriptional factors responding to the starvation have also been extensively examined [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%